Weight-bearing computed tomography versus standard imaging for the evaluation of complex foot and ankle pathology: a systematic review and meta-analysis on the change in surgical planning and diagnostic accuracy - Vera, Jorge Leonardo Fabara; Rodríguez, Andrés Felipe Pérez; Mazo, Berenice Baños del; Tafur, Elkin Armando Gallo; González, Wendy Reyna; Granados, Ana Sofía Carreño; Valdés, Claus André James; Campos, David Suárez (International Journal of Research in Orthopaedics, 2026)
Weight-bearing computed tomography (WBCT) is a paradigm change in imaging of the musculoskeletal system, as it records the foot and ankle in physiologic load. This systematic review is a critical appraisal of the diagnostic superiority and its impact on surgical decision-making of WBCT versus standard imaging (SI: radiographs and non-weight bearing CT) for complex foot and ankle conditions. Fifteen studies were included after a search of the literature, adherence to the PRISMA translation. A narrative synthesis and, where possible, a quantitative analysis was conducted. WBCT consistently showed significantly greater magnitude of deformity in conditions such as adult acquired flatfoot deformity (e.g., medial cuneiform-to-floor distance was reduced from 29 mm NWB to 18 mm WB) and highly reliable 3D biometrics (e.g., Foot and Ankle Offset ICCs 0.97 to 0.99). For Lisfranc injuries, WBCT was more sensitive for the detection of subtle instability. Crucially, WBCT was responsible for changing the surgical plan in a pooled 32% of cases (95% confidence interval (CI): 24–41%) with the most common changes made being addition or alteration of procedures. The quality of the included cohort studies was moderate and randomized trials showed some concerns regarding bias. While the technology provides better diagnostic insight and modification of preoperative planning in a large proportion of patients, the supporting evidence is largely from moderate quality, heterogeneous studies with a dearth of long-term outcome data. WBCT is an effective tool for assessment of load-dependent pathology and its incorporation of the diagnostic pathway for complex deformity and instability would seem to be justified.